2013
DOI: 10.1093/nar/gkt464
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal deletions and inversions mediated by TALENs and CRISPR/Cas in zebrafish

Abstract: Customized TALENs and Cas9/gRNAs have been used for targeted mutagenesis in zebrafish to induce indels into protein-coding genes. However, indels are usually not sufficient to disrupt the function of non-coding genes, gene clusters or regulatory sequences, whereas large genomic deletions or inversions are more desirable for this purpose. By injecting two pairs of TALEN mRNAs or two gRNAs together with Cas9 mRNA targeting distal DNA sites of the same chromosome, we obtained predictable genomic deletions or inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
259
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(268 citation statements)
references
References 52 publications
6
259
0
3
Order By: Relevance
“…Importantly, we have demonstrated that the Dusp6 mutations can be transmitted to the next generation with high efficiency. Moreover, we are the first to show that a simultaneous microinjection of 2 gRNA molecules leads to large DNA fragment deletions in the rat genome as reported in zebrafish [15]. The latter enables genetic elimination of a whole exon or even an entire gene including genes for non-coding RNAs, which is particularly useful for studying the functions of non-coding RNAs.…”
Section: Dear Editormentioning
confidence: 75%
“…Importantly, we have demonstrated that the Dusp6 mutations can be transmitted to the next generation with high efficiency. Moreover, we are the first to show that a simultaneous microinjection of 2 gRNA molecules leads to large DNA fragment deletions in the rat genome as reported in zebrafish [15]. The latter enables genetic elimination of a whole exon or even an entire gene including genes for non-coding RNAs, which is particularly useful for studying the functions of non-coding RNAs.…”
Section: Dear Editormentioning
confidence: 75%
“…Several studies indicate that simultaneous targeting of two loci using two pairs of TALENs can induce large genomic deletions [34][35][36][37], inversions as well as chromosomal translocations [38,39]. Using this dual TALEN approach, we and other groups have demonstrated that large deletions of 1-80 kb can be efficiently created in zebrafish [33,[40][41][42]. These large deletions have been used to knock out non-coding RNA genes, gene clusters and gene regulatory elements.…”
Section: Introductionmentioning
confidence: 99%
“…These programmable RNA-guided endonucleases (RGEN) are composed of two RNA elements, the CRISPR RNA (cRNA) and its transactivating RNA (tracRNA), which can be fused together through a linker sequence to provide greater flexibility both in the design and applicability of this technology 7 . The CRISPR-Cas9 system has been applied into a variety of gene modification processes in human cells, including targeted genome engineering 8,9 , transactivation and silencing module factors 10 , and genetic correction 11 , and has even been used as a platform to induce large chromosomal deletions or inversions 9,12 . However, to our knowledge CRISPR-Cas9 technology has not yet been adapted to generate human chromosomal translocations.…”
mentioning
confidence: 99%